Bayesian Methods for Obtaining X-bar Chart: An Application on Food Quality Control - Khatiwada, Ram Prasad (Journal of Institute of Science and Technology, 2015)
This article is about the Bayesian methods of constructing control chart for process mean. The control chart for mean based on the use of normal prior distribution seems to be robust for normal observations. The concussion is derived from an experiment of a set of real dada of the weights of a food product filled in pouches. The results were also supported by the simulated data. Journal of Institute of Science and Technology, 2014, 19(2): 100-104